Hypomyelination with Atrophy of Basal Ganglia and Cerebellum (HABC) Due to UFM1 Mutation in Roma Patients - Severe Early Encephalopathy with Stridor and Severe Hearing and Visual Impairment. A Single Center Experience - Ivanov, Ivan; Pacheva, Iliyana; Yordanova, Ralitsa; Sotkova, Iglika; Galabova, Fani; Gaberova, Katerina; Panova, Margarita; Gheneva, Ina; Tsvetanova, Tsvetelina; Noneva, Katerina; Dimitrova, Diana; Markov, Stoyan; et al. (CNS & Neurological Disorders - Drug Targets, 2023)
Background: Hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC) is a neurodegenerative disease with neurodevelopmental delay, motor, and speech regression, pronounced extrapyramidal syndrome, and sensory deficits due to TUBB4A mutation. In 2017, a severe variant was described in 16 Roma infants due to mutation in UFM1. Objective: The objective of this study is to expand the clinical manifestations of H-ABC due to UFM1 mutation and suggest clues for clinical diagnosis. Methodology: Retrospective analysis of all 9 cases with H-ABC due to c.-273_-271delTCA mutation in UFM1 treated during 2013-2020 in a Neuropediatric Ward in Plovdiv, Bulgaria. Results: Presentation is no later than 2 months with inspiratory stridor, impaired sucking, swallowing, vision and hearing, and reduced active movements. By the age of 10 months, a monomorphic disease was observed: microcephaly (6/9), malnutrition (5/9), muscle hypertonia (9/9) and axial hypotonia (4/9), progressing to opisthotonus (6/9), dystonic posturing (5/9), nystagmoid ocular movements (6/9), epileptic seizures (4/9), non-epileptic spells (3/9). Dysphagia (7/9), inspiratory stridor (9/9), dyspnea (5/9), bradypnea (5/9), apnea (2/9) were major signs. Vision and hearing were never achieved or lost by 4-8 mo. Neurodevelopment was absent or minimal with subsequent regression after 2-5 mo. Brain imaging revealed cortical atrophy (7/9), atrophic ventricular dilatation (4/9), macrocisterna magna (5/9), reduced myelination (6/6), corpus callosum atrophy (3/6) and abnormal putamen and caput nuclei caudati. The age at death was between 8 and 18 mo. Conclusion: Roma patients with severe encephalopathy in early infancy with stridor, opisthotonus, bradypnea, severe hearing and visual impairment should be tested for the Roma founder mutation of H-ABC in UFM1.
Keywords: paroxysmal